Language, Music and Emotion in Lament Poetry : The Embodiment and Performativity of Emotions in Karelian Laments - Silvonen, Viliina; Stepanova, Eila (2021)
This chapter focuses on the expression, conveyance, performance, and emergence of emotions in lament poetry. We analyze laments from verbal, musical, aural, and thematic perspectives and discuss the emotions as a phenomenon and a process in which sociocultural and neurobiological aspects are interdependent. During the lament performance, the emotional state of lamenter usually intensifies. The multimodal techniques and various expressional characteristics of laments increase the emotional intensity either socioculturally or via neural-physiological feedback system. In laments, the embodiment, expression, and emergence of emotion interweave; the features that express and convey emotions also performatively raise them. Peer reviewed